Soil physicochemical properties and their significance for sustainable sugarcane production in Kesem Allaideghe plains irrigation project area, Eastern Ethiopia - Pal, Dhan; G. Selassie, Yihenew (Ethiopian Journal of Science and Technology, 2025)
A feasibility study was carried out to assess the suitability of Allaideghe plains, located in middle awash valley, for the cultivation of sugarcane plantation. The project area, covering 38000 ha, lies between 9o 07’ to 9o 26’ N latitude and 40o 30’ to 40o 50’ E longitude. A detailed soil survey was carried out on 500 m x 500 m grid consisting 1520 auger holes and 76 soil profile observations. The soils of the entire project area were very deep (>200 cm). The textural classes included silty clay loam, clay and heavy clay which revealed that texture varied from fine to very fine with high clay content. Soil reaction (pH), electrical conductivity of saturated extract (ECe), exchangeable sodium percentage (ESP), cation exchange capacity (CEC), organic carbon (OC), CaCO3 ranged between 7.7 to 8.2, 0.9 to 8.0 dS m-1, 9.9 to 42.7%, 40.6 to 61.7 cmol (+) kg-1, 0.3 to 1.2 g kg-1, and 8.3 to 18.3 %, respectively. Soluble cation contents of Na, Mg, Ca and K varied from 8.5 to 20.2, 0.2 to 2.6, 4.7 to 12.6, and 0.1 to 0.2 meq l-1, respectively. Major hydraulic properties influencing water availability and irrigation scheduling for sugarcane included infiltration rate and hydraulic conductivity. Basic infiltration rate varied from 0.2 to 6.2 cm h-1 and in-situ hydraulic conductivity varied from 0.07 to 0.60 m d-1. Low hydraulic conductivity may cause waterlogging in the project area. In order to improve soil structure and water availability, addition of gypsum, plant residues and organic matter are recommended.